Controlling gminy - Borowiec, Leszek (Controlling Communites, 2005)
Comune is an autonomic territory. Innovative processes are required for the organisation to function effectively - strategic Controlling is required. Effective management of the organisation requires the usage of adequate tools and methods. One of these tools is the Balanced Scorecard. This tool is used with good results all around the world in both governmental and non governmental agencies, as well as in non profit institutions. The basis of forming a balanced card of deeds is a mission and stratergy. From every perspective a system of goals is formed. The four main perspectives taken into account are: financial perspectives, the clients perspective, internal processes as well as learning and growth. Ignoring and not taking into account these important issues leads to the ineffective running and functioning of the community.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 79-93